Assessment of distribution of two sympatric mud crab species – Panopeus americanus and Panopeus austrobesus – in a Western Atlantic estuarine intertidal zone - Saraiva, Gabriel L. [UNESP]; Moreira, Leonardo [UNESP]; Mantelatto, Fernando L.; Costa, Rogerio C. [UNESP]; Pescinelli, Régis A. (FapUNIFESP (SciELO), 2024)
Sympatric mud crab species Panopeus americanus and Panopeus austrobesus are found in intertidal environments associated with muddy and rocky habitats in the Western Atlantic coast. Therefore, they are a suitable model system to be used in studies focused on investigating biological coexistence aspects between close species, such as population structure and habitat. The aims of the current study are to describe and compare the distribution of two sympatric mud crab species – P. americanus and P. austrobesus – based on their spatial and temporal distribution, in a low human impact estuarine complex area. The hypothesis that these two species show similar distribution, although one species is more abundant than the other, was herein tested. Sampling was carried out in the intertidal zone of a specific area in Cananeia estuarine complex, São Paulo State, Southeastern Brazil, in different periods of time for two years. Both species presented similar pattern distribution and frequency, with predominance in the middle and high intertidal zones, including all demographic categories. However, Panopeus americanus was more abundant and presented smaller mean size in all sampling zones. The pronounced disparity in size between the species suggests divergent dietary preferences, potentially related to prey size allowing the coexistence of these sympatric and syntopic species. The predominance of these two species in the upper intertidal zones was understood as a strategy for avoiding competition with the intertidal alpheid shrimps.
Avaliação da distribuição de duas espécies simpátricas de caranguejo-da-lama – Panopeus americanus e Panopeus austrobesus – em uma zona intertidal estuarina do Atlântico Ocidental
Keywords: Brachyura; coexisting species; microhabitat distribution; Panopeidae